Kepastian Hukum Atas Jual Beli terhadap Pembeli yang Belum Melakukan Balik Nama Berdasarkan Peralihan Hak yang Dibuat di Bawah Tangan: Penelitian - Rizky Kurnia Sani; Anriz Nazaruddin Halim; Refki Ridwan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Sale and purchase transactions serve as one of the legal mechanisms through which individuals may acquire land ownership. The research method employed is normative juridical. The findings of this study reveal that title transfer based on private transactions that have not been registered by the buyer cannot be directly executed, as it fails to meet the formal legal requirement of an authentic deed issued by a Land Deed Official (Pejabat Pembuat Akta Tanah, PPAT) as the legal basis for the transfer of land rights. Private agreements hold evidentiary value only as civil contracts and cannot independently serve as a valid legal basis for the transfer of land title in official land records. In order for the buyer to obtain legal recognition and certainty, further legal steps are required, including the preparation of an official sale and purchase deed, fulfillment of administrative requirements, and registration of the transfer of rights at the local land office. Consequently, legal certainty for buyers who have not yet conducted title transfer based on a private deed remains legally vulnerable.